2018
DOI: 10.1007/s00038-018-1116-4
|View full text |Cite
|
Sign up to set email alerts
|

“I am spiritual, but not religious”: Does one without the other protect against adolescent health-risk behaviour?

Abstract: Our findings suggest that high spirituality only protects adolescents from HRB if combined with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
(43 reference statements)
3
15
0
2
Order By: Relevance
“…Especially in a secular environment, this situation could be difficult for adolescents surrounded by their non-religious peers. This explanation is also supported by other studies on R/S in Czech adolescents, which reported that attending non-spiritual adolescents showed a higher health-risk behavior [15] and that religious attendance was significantly associated with more difficult communication with the mother [29]. In addition, other studies have reported possible damaging effects of family arguments about religion on a child's development [30].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Especially in a secular environment, this situation could be difficult for adolescents surrounded by their non-religious peers. This explanation is also supported by other studies on R/S in Czech adolescents, which reported that attending non-spiritual adolescents showed a higher health-risk behavior [15] and that religious attendance was significantly associated with more difficult communication with the mother [29]. In addition, other studies have reported possible damaging effects of family arguments about religion on a child's development [30].…”
Section: Discussionsupporting
confidence: 72%
“…Research suggests that religiosity and spirituality have positive effects on adolescent health attitudes or behaviors [13]. Spirituality (distinctly and in relation to religiosity) has been shown to be associated with the healthy development of adolescents [14] and their lower health-risk behavior [15]. It has further noted their more active ways of spending leisure time [16], with an enhanced ability to cope and with positive outcomes in mental health, psychological well-being, and academic learning [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the main analysis, spirituality was assessed as a scale variable in order to prevent a loss of information. However, according to previous studies [10,31], spirituality was also dichotomized for sensitivity analysis (graphical representation), and participants with a score of 34 or higher (upper quartile of the score) were considered as spiritual, and the rest as non-spiritual. Cronbach’s alpha was 0.81 in our sample for the total scale, for the RWB it was 0.93, and for the EWB 0.76.…”
Section: Methodsmentioning
confidence: 99%
“…Zinnbauer and Pargament [8] summarized the definitions of religiosity and spirituality and concluded that the usefulness of polarizing religiosity and spirituality is unclear and that differences between the two will continue to be identified. In empirical research, religiosity and spirituality are sometimes treated as one factor in order to derive a composite score for general religiosity (e.g., [9]) and are sometimes compared with each other (e.g., [10]). Within the context of health-related outcomes of religiosity and spirituality in adolescents, the study of Malinakova et al [10] showed that mere religious attendance and spirituality were associated with a decreased risk of only one or two kinds of health-risk behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation